A Case Study Approach to Exploring Resilient Pedagogy During Times of Crisis - Katie Clum; Elizabeth Ebersole; David Wicks; Munyi Shea (Online Learning, 2022)
In response to the COVID-19 pandemic of 2020 and the ensuing public health crisis, thousands of higher education institutions (HEIs) worldwide have had to grapple with rapid pivots to emergency remote online learning modalities with relatively little time to prepare, and the need to maintain these modalities continues to extend longer than most institutions anticipated. However, this is not the first time HEIs have had to enact an emergency switch to online learning in a time of crisis, and there is perhaps much to be learned from examining the experiences of institutions that have been through this before. Resilient pedagogy is an emerging field in education, but it is intrinsically tied to online learning in a crisis insofar as it describes the ability to intentionally and effectively shift instructional tactics given a change in environment or context. Using a case study approach, this paper explores indicators of resilient pedagogy in emergency pivots to online learning following crisis situations—including the COVID-19 pandemic—in the United States, New Zealand, and South Africa. The data informing this research are qualitative, derived from interviews with faculty members and students in each higher education context.